Sirtuins and Disease: The Road Ahead - Carafa, Vincenzo; Nebbioso, Angela; Altucci, Lucia (Frontiers in Pharmacology, 2012)
Sirtuins represent a promising new class of conserved histone deacetylases, originally identified in yeast. The activity of the sirtuin (SirT) family – made up of seven members (SirT1-7) – is NAD+ dependent. Sirtuins target a wide range of cellular proteins in nucleus, cytoplasm and mitochondria for post-translational modification by acetylation (SirT1, 2, 3 and 5) or ADP ribosylation (SirT4 and 6). Sirtuins regulate responses to stress and ensure that damaged DNA is not propagated, thus contrasting the accumulation of mutations. To date, sirtuins have emerged as potential therapeutic targets for treatment of human pathologies such as metabolic, cardiovascular and neurodegenerative diseases, and cancer. SirT1 is the founding member of this class of enzymes and is currently the best known of the group. SirT1 acts in various cellular processes, deacetylating both chromatin and non-histone proteins, and its role in cancer and aging has been extensively studied. SirT1 may play a critical role in tumor initiation and progression as well as drug resistance by blocking senescence and apoptosis, and by promoting cell growth and angiogenesis. Recently, growing interest in sirtuin modulation has led to the discovery and characterization of small molecules able to modify sirtuin activity. The present review highlights SirT mechanism(s) of action and deregulation in cancer, focusing on the therapeutic potential of SirT modulators both in cancer prevention and treatment.